Conceptual foundations of innovation systems - Jorge Bateira (The University of Manchester, Manchester Business School, 2009)
Production' and 'transfer' of knowledge, and the role of institutions, are two major conceptual tenets of Innovation Systems (IS) literature, which flourished in the evolutionary stream of economics since the eighties of last century. Building on results of different disciplines, the paper critically discusses 'knowledge' and 'institution' concepts used in that literature and presents alternative meanings supported by emergentist ontology of persons, social and cultural phenomena. The paper discusses how such conceptual framework matters for the analysis of innovation processes and what are its policy implications.
Keywords: 330; innovation systems; knowledge; institutions; evolutionary economics; Innovation; Wissenstransfer; Institutionalismus; Evolutionsökonomik